Rancangan Instrumen Virtual Kendang Sunda Menggunakan Kontakt Sebagai Media Kreativitas Musik Digital - Aditya Pratama; Diah Latifah (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2023)
Purpose: The purpose of this research is to reveal the process of designing a virtual instrument for Sundanese drumming, starting from practical studies to its realization as a market-ready design. The influence of the development of digital music technology has led to various inventions in the form of virtual instruments. As part of the preservation and development of local culture-based music, it is necessary to create virtual musical instruments, including Sundanese drums. The problem that occurs today is, that virtual instrument media for Sundanese drums that facilitate learning Sundanese drums is still very rare. Method: The method is practice-led research or practice-based study by playing real drumming instruments recorded using sampling media in the form of virtual instruments in the KONTAKT Library. Result and Discussion: The design process is carried out in three stages, namely. pre-production, production, and post-production. The results showed that the pre-production analysis of tepak kendang sunda highlighted four drum sounds, namely keplak, kentrung, kemprang, and gedug. The production stage shows that the results of the tepak kendang analysis were recorded and produced a variety of different selected drum sounds. Conclusion: The sound samples were arranged in a keymap system on the KONTAKT keyboard, based on a velocity range system, so that each sound type expression can function as a virtual instrument in a DAW (digital audio workstation) application via midi. Pre-production alpha testing results with two phases state that the virtual instrument of the Sundanese drum can run well. The implication of the product design of the virtual instrument of Sundanese drums is adequate and ready to be used as a means of creativity in digital music.